OpenCV 3 computer vision with Python cookbook : leverage the power of OpenCV 3 and Python to build computer vision applications /: leverage the power of OpenCV 3 and Python to build computer vision applications. (2018) - Spizhevoy, Alexey; Rybnikov, Aleksandr
No abstract available